Effectiveness of the Family Hope Program in Ketapang Village, Panjang District in 2022 - Maulidi Ramadhan, Deri; Wahyudi, Heru; Ciptawaty, Ukhti (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to analyze the effectiveness of the Family Hope Program for poor communities in Bandar Lampung City. This type of research is qualitative descriptive research. This research uses primary data. The data collection methods used in this research are observation, interviews, documentation and questionnaires, as well as using Validity tests and Reliability tests. Data processing methods in this research use editing, coding, scoring and tabulation. The results of this research were 54.60% which was included in the effective category.